Correlation between matrix metalloproteinase-2 polymorphisms and first and recurrent atherosclerotic ischemic stroke events: a case–control study. Issue 6 (June 2021) - Li, Ying; Ouyang, Qing-rong; Li, Juan; Chen, Xiao-rong; Li, Lin-lin; Xu, Lei; Yu, Ming
Objective: To determine the associations between matrix metalloproteinase-2 (MMP-2, encoded by the MMP2 gene) 1306C/T and 735C/T polymorphisms and first and recurrent ischemic stroke in a Chinese population. Methods: Patients with first and recurrent ischemic stroke were included. Serum MMP-2 was measured, and MMP2 1306C/T and 735C/T polymorphisms were detected. The associations between MMP2 1306C/T and 735C/T polymorphisms and first and recurrent ischemic stroke were analyzed. Results: Serum MMP-2 in patients with first and recurrent ischemic stroke was significantly higher compared with controls, and patients with recurrent ischemic stroke had higher MMP-2 than those with first ischemic stroke. The frequency of the CC genotype and C allele of MMP2 735C/T was highest in patients with recurrent ischemic stroke, followed by patients with first ischemic stroke, and controls. Conversely, the genotype and allele of MMP2 1306C/T did not significantly differ between groups. The CC genotype of MMP2 735C/T was independently associated with first and recurrent ischemic stroke (odds ratios = 1.45 and 1.64, respectively), as was the C allele of MMP2 735C/T (odds ratios = 1.68 and 1.77, respectively). Conclusions: The CC genotype and C allele of MMP2 735C/T were associated with first and recurrent ischemic stroke in a Chinese population.